Recent development of nuclear study using electron and photon beams - Korea-Japan Joint Symposium on Recent Development of Nuclear Study Using Electron and Photon Beams (1994 : Korea); Cheon, Il-Tong (River Edge, NJ : Global Publication Services, 1995)
40